The Role of microRNAs, Long Non-coding RNAs, and Circular RNAs in Cervical Cancer - Tornesello, Maria Lina; Faraonio, Raffaella; Buonaguro, Luigi; Annunziata, Clorinda; Starita, Noemy; Cerasuolo, Andrea; Pezzuto, Francesca; Tornesello, Anna Lucia; Buonaguro, Franco Maria (Frontiers in Oncology, 2020)
Prolonged infection of uterine cervix epithelium with human papillomavirus (HPV) and constitutive expression of viral oncogenes have been recognized as the main cause of the complex molecular changes leading to transformation of cervical epithelial cells. Deregulated expression of microRNAs (miRNA), long non coding RNAs (lncRNA) and circular RNAs (circRNA) is involved in the initiation and promotion processes of cervical cancer development. Expression profiling of small RNAs in cervical neoplasia revealed up-regulated “oncogenic” miRNAs, such as miR-10a, miR-21, miR-19, and miR-146a, and down regulated “tumour suppressive” miRNAs, including miR-29a, miR-372, miR-214 and miR-218, associated with cell growth, malignant transformation, cell migration and invasion. Also several lncRNAs, comprising among others HOTAIR, MALAT1, GAS5 and MEG3, have shown to be associated with various pathogenic processes such as tumor progression, invasion as well as therapeutic resistance and emerged as new diagnostic and prognostic biomarkers in cervical cancer. Moreover, human genes encoded circular RNAs, such as has_circ-0018289, have shown to sponge specific miRNAs and to concur to the deregulation of target genes. Viral encoded circE7 has also demonstrated to overexpress E7 oncoprotein thus contributing to cell transformation. In this review, we summarize current literature on the complex interplay between miRNAs, lncRNAs and circRNAs and their role in cervical neoplasia